Outcomes of Distal Radial Fractures in Geriatric Patients Following Volar Locked versus Dorsal Bridge Plating - Dondapati, Akhil; Carroll, Thomas J.; Patel, Urvi; Hammert, Warren C.; Gonzalez, Ronald; Ketonis, Constantinos (Journal of Wrist Surgery, 2025)
Volar locked plating (VLP) and dorsal bridge plating (DBP) are commonly used fixation techniques for distal radial fractures (DRFs). In patients older than 65 years, DRFs account for more than 18% of all fractures; however, a comparison of outcomes of these techniques in the geriatric population is absent.The purpose of our study was to use propensity score matching to compare both clinical and radiographic outcomes of VLP and DBP fixation of DRF in geriatric patients ≥65 years.In total, 2,181 patients at least 65 years old with closed DRFs were retrospectively analyzed. Wrist range of motion (ROM) and radiographic outcome data were calculated at 6-month follow-up. Patient Reported Outcomes Measurement Information System (PROMIS) Upper Extremity (UE), Physical Function (PF), and Pain Interference (PI) were calculated at each follow-up visit. Injury characteristics, surgical complications, and patient demographic data were also analyzed. A combination of propensity score matching, multivariate analysis, t-test, and chi-square tests were used to conduct the statistical analysis.After propensity matching, a total of 1,375 patients underwent VLP, whereas 275 patients underwent DBP. Within the univariate analysis, the DBP demonstrated a higher proportion of AO Foundation/Orthopaedic Trauma Association (AO/OTA) 23-C fracture patterns, with fewer AO/OTA 23-A compared with VLP (p < 0.05). Multivariate analysis demonstrated greater wrist flexion and extension, radial and ulnar deviation, supination, pronation, and grip strength, and higher PROMIS PF and PI among the VLP group (p < 0.05). At 6-month follow-up, VLP patients demonstrated greater radial inclination (21.2 vs. 20.3 degrees), lower articular step-off (0.76 vs. 0.86 mm), with similar volar tilt and radial height (p > 0.05). DBP patients had higher rates of malunion (6.2 vs. 3.0%), nonunion (4.0 vs. 2.0%), and tendon rupture (2.5 vs. 0.9%) but similar rates of revision surgery and infection (p > 0.05).VLP was associated with greater wrist flexion, extension, radial deviation, ulnar deviation, supination, pronation, grip strength, and PROMIS PF and PI compared with DBP. There were significantly higher complication rates with DBP; however, there was a similar rate of revision surgery. While the VLP group showed significantly greater ROM and radiographic outcomes, this likely did not represent a clinically significant difference in this population.Therapeutic III.
Keywords: distal radius fractures; volar locked plating; dorsal bridge plating; geriatrics; outcomes